PENERAPAN METODE PELATIHAN PLIOMETRIK DALAM MENINGKATKAN POWER OTOT TUNGKAI ATLET PPLM BALI - Suratmin, Suratmin (Journal of Physical Education Health and Sport, 2016)
The purpose of this study was to assess and prove the application of plyometrics training methods to improve limb muscle power athletes PPLM Bali. The research method using a quasi-experimental methods. The results showed that: (1) there is a significant improvement between the initial tests and final test against power leg muscle with a test jump upright, (p 0.008), (2) there is a significant improvement between the initial tests and final test against power leg muscle with a test jump upright, laboratory tests (p 0.003), (3) there is a significant improvement between the initial tests and final test against power leg muscle with a test jump upright, field tests of 8.64%, (4) there is a significant increase between tests initial and final test against power leg muscle with a test jump upright, laboratory tests for 5:04%, (5) there is a significant improvement between the initial tests and final test against power leg with a test jump without prefix / standing broad jump (p 0.000), and (6) there is a significant improvement between the initial test and final test against power leg with a diving tests without prefix / standing broad jump of 23%. Concluded there is a significant improvement between the initial test and final test against leg muscle power.